Pengaruh Harga, Lokasi dan Suasana Toko Terhadap Keputusan Pembelian - Surya Wahyu Prasetya; Retno Susanti; Lamidi Lamidi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the significance of the influence of price, location, and store atmosphere on customer purchasing decisions at Harno Surya stores. A quantitative research approach was employed, utilizing primary data as the main source of information. The study population consisted of customers who had shopped at Harno Surya stores, although the exact number was unknown. A sample of 176 respondents was selected using a purposive sampling technique. Data collection methods included questionnaires, literature review, and observation. The collected data were analyzed using descriptive analysis, multiple linear regression analysis, t-test, F-test, and the coefficient of determination test.The results of the multiple linear regression analysis produced the equation: Y = 0.534 + 0.181X₁ + 0.426X₂ + 0.329X₃, indicating that price (X₁), location (X₂), and store atmosphere (X₃) all contribute positively to purchasing decisions (Y). The t-test results demonstrated that each independent variable had a significant effect on purchasing decisions. Furthermore, the F-test results showed an F-value of 157.276 with a significance level of 0.000 (<0.05), confirming that the regression model is appropriate for predicting the impact of price, location, and store atmosphere on purchasing decisions. The coefficient of determination (R²) was 0.728, suggesting that 72.8% of purchasing decisions were influenced by the three independent variables, while the remaining 27.2% was influenced by other factors not included in this study.These findings highlight the importance of price, location, and store atmosphere in shaping consumer purchasing decisions, offering valuable insights for retailers seeking to enhance their marketing strategies and store management.